Team‐based parent training by child specialists helps maltreated children. Issue 12 (25th December 2018) - Yokoyama, Hiroyuki; Tomizawa, Yayoi; Sato, Yoshinori; Kobayashi, Atsuko; Katsushima, Yuriko; Katsushima, Fumio
Abstract: Background: This study assessed the effects of the parent training (PT) technique, in which child specialists (CS) such as preschool and school teachers promote secure attachment in children with aberrant social behavior following maltreatment, using a team approach. Methods: Child specialists confirmed the presence of child abuse, according to Japanese Ministry of Health, Labour and Welfare criteria. CS such as homeroom, special education‐related, student guidance‐related, nursing teachers and co‐workers received a PT course conducted by the authors. A homeroom teacher provided classroom management to model good examples of social life for the target child. A nursing teacher and assistant offered individualized instruction to foster the formation of secure attachments by the target child. Result: Behavioral abnormalities in both school and home resolved in seven out of 12 cases. These subjects received the intervention for 2–4 years. In the other cases, behavioral abnormalities disappeared or decreased at school, but continued at home. Almost all children met the alternative criteria of attachment disorder proposed by Boris and Zeanah. One child met the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM‐IV‐TR) criteria for reactive attachment disorder. This intervention is significantly more effective for children who have yet to begin elementary school than those in elementary school. Conclusions: The PT technique as applied by CS using a team approach may be a useful intervention for fostering secure attachment in children with maltreatment who exhibit behavioral abnormalities. Early detection and intervention are necessary to successfully address the behavioral abnormalities of children with maltreatment.